Adsorption separation of ethyleneethane - Nassara, Ramiel (University of Ottawa (Canada), 2008)
To offset rising energy costs, it is becoming a necessity to lower energy usage within industrial processes. Such can be said for the separation of olefin/paraffin mixtures. An example of such a mixture is ethylene/ethane. This highly energy intensive industrial separation employs cryogenic distillation to achieve a high purity product. Subsequently, the energy cost to run such a system is extremely high. Hybrid scenarios have been explored, with adsorption being a potential candidate. This work studied the potential of three adsorbents for the separation of ethylene/ethane: AgNO3/SiO2, CuCl/SiO 2, and CECA 13X. AgNO3/SiO2 and CuCl/SiO 2 were both prepared in the laboratory. Pure component constant volume experiments were conducted, along with binary mixture predictions for all three adsorbents at 3 different temperatures. The expected working capacities were also calculated for the three adsorbents. Finally, an economic analysis, without taking competitive adsorption in to factor, was conducted to give a rough idea of how much a potential PSA system would cost using the three adsorbents individually. CuCl/SiO2 yielded the most favorable results of the three adsorbents, but more studies were determined necessary on the optimization of the preparation of the adsorbent. AgNO3/SiO 2 was not completely ruled out, however. Both the adsorbents showed characteristics for a potential use within industry. CECA 13X was not considered a viable candidate for such a separation.
Keywords: Engineering, Chemical.